Advances in Drug Delivery via Biodegradable Ureteral Stent for the Treatment of Upper Tract Urothelial Carcinoma - Shan, Hongli; Cao, Zhongshuai; Chi, Changliang; Wang, Jixue; Wang, Xiaoqing; Tian, Jingyan; Yu, Bing (Frontiers in Pharmacology, 2020)
Drug eluting ureteral stent is an effective mean for local drug delivery to the urinary tract. It can potentially solve a variety of upper urinary tract problems, such as stent-related urinary tract infections and discomfort, ureteral stricture, and neoplastic diseases. However, the release of drugs elutes on the surface of biostable stents is unsustainable and uncontrollable. With the development of biomaterial science, the emergence of biodegradable ureteral stents (BUS) provides a new approach for local drug delivery in urinary tract. The drugs can be continuously released in a controlled manner from a drug-eluting BUS, when the stent degrades. Especially for the delivery of antitumor drugs, the stents can obviously improve the therapeutic effectiveness of the drugs by prolonging the contact duration of the drug and tumor cells. In addition, a secondary stent removal procedure can be avoided. The purpose of this review article is to provide an overview of anti-tumor drug-eluting BUS and discuss the biomaterials and drug delivery system of BUS that are currently being developed to deliver anti-tumor drugs for upper tract urothelial carcinoma.